Electronic spectrum and superconductivity in Hubbard model - Plakida, N.M.; Oudovenko, V.S. (Condensed Matter Physics, 2008)
A microscopic theory of electronic spectrum and superconducting pairing within the Hubbard model is formulated.
The Dyson equation for the normal and anomalous Green functions in terms of the Hubbard operators
is derived by applying the Mori-type projection technique. The self-energy is evaluated in the noncrossing
approximation for electron scattering on spin and charge fluctuations induced by kinematic interaction for
Hubbard operators. Numerical results for electron dispersion in the strong correlation limit are presented.
Superconducting pairing mediated by antiferromagnetic exchange and spin fluctuations is discussed. В рамках моделi Хаббарда, сформульовано мiкроскопiчну теорiю електронного спектру та надпровiдного спарювання. З використанням технiки проектування типу Морi, отримано рiвняння Дайсона для нормальних i аномальних функцiй Ґрiна побудованих на операторах Хаббарда. Власноенергетична частина розрахована в наближеннi без перетинiв для розсiяння електронiв на спiнових i зарядових флуктуацiях, якi створюються кiнематичною взаємодiєю для операторiв Хаббарда. Приведенi чисельнi результати для електронної дисперсiї в границi сильних кореляцiй. Обговорюється можливiсть надпровiдного спарювання через антиферомагнiтнi обмiннi та спiновi флуктуацiї.